Measurement, modelling and uncertainty propagation of low-pressure phase equilibrium data for 1-alcohols and n-alkanes - Buitendach, Nadine (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024.